Reconstruction Reconsidered: Thomas Adams’s Role in Rebuilding the “Devastated Area” after the 1917 Halifax Disaster - Cahill, Barry (Urban History Review / Revue d'histoire urbaine)

(untitled) (Urban History Review / Revue d'histoire urbaine, 2018)
Though English urban planner Thomas Adams’s connection with reconstruction after the 1917 Halifax Disaster (“Halifax Explosion”) is well known, the precise nature and extent of his involvement has not been subject to rigorous research or informed analysis and, as a result, is neither known nor understood. Perhaps least-known is Adams’s crucial working relationship with the Halifax Relief Commission, the federal government body set up seven weeks after the disaster to take complete charge of emergency management. This article addresses a significant lacuna in early Canadian planning history as well as in the history of recovery from the Halifax Disaster. The history of reconstruction itself, which has yet to be written, can ill-afford to magnify or misrepresent Adams’s significant contribution to it.